STRATEGI PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT PESISIR - Ulfah Attamimi; Muhammad Ihsan Mattalitti; Riston G. Ahmad (Halu Oleo University, 2024)
This research documents the strategies implemented by the Lemo village government to empower the seaweed farming community. Through a qualitative descriptive approach, data was collected through observation and interviews with 6 informants covering various roles in village government and society. The findings show that the Lemo village government implemented a strategy based on improving the quality of human resources, strengthening potential, and developing farmer groups. This analysis discusses the impact of this strategy on people's knowledge, skills, and awareness of seaweed cultivation, as well as its implications for the independence and welfare of coastal communities.